HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN PERILAKU BULLYING PADA REMAJA - Riyanto Riyanto; Kamsari Kamsari; Siti Khodijah (JURNAL KESEHATAN INDRA HUSADA, 2022)
bullying behavior which is all forms of oppression or violence that is carried out intentionally by one or a group of people who are stronger or more powerful towards others where bullying behavior is caused by poor parenting in educating teenagers. In addition, bullying behavior can be carried out directly in the form of verbal bullying and nonverbal/nonphysical bullying.The purpose of this study was to determine the relationship between parenting and bullying behavior in adolescents. This study uses a systematic literature review method that combines literature search and selection based on Preferred Reporting Items for Systematic Reviews and Meta analyzes (PRISMA). In the process of identifying the literature, it uses relevant keywords. The results of 4 articles research show that there is a relationship between parenting patterns and bullying behavior in teenagers. Whereas, 1 article shows that there is no relationship between parenting patterns and bullying behavior in teenagers, because there are several other factors that influence but cannot be controlled. The conclusion of this study is that parenting is related to bullying behavior in teenagers. However, the suggestions addressed to parents should be more concerned with their children, so that they can avoid bullying behavior both as victims or perpetrators, as well as there must be an active role for parents in increasing children's confidence.